Knowledge Integration Through ‘e kalpa’- a Cloud Based Interactive Mobile App for Coconut Farmers - P., Anithakumari; Sit, Arun Kumar; B., Midhun (International Journal of Economic Plants, 2021)
Coconut based farming system is the major livelihood option of small and marginal farm families. Major coconut growing states had high literacy rate and tele density more than 100%. Studies reported low level of ICT use among the coconut farmers. ICAR CPCRI developed the first cloud based interactive mobile app for the mandate crops such as coconut, areca nut and cocoa for the national level stakeholders. A participatory study was conducted during 2017-20 in Alappuzha district to evolve an ICT strategy for coconut community and to develop an interactive multilingual mobile application customized to farmers of different states. ‘e kalpa’ app is refined with components such as knowledge base, field issue management, synchronized farming, input calculator and crop information. It is accessible in online and offline mode and available free of cost in Google play store. Real time reporting of field problems in audio, video or image modes and direct interaction with experts of CPCRI is the unique feature of value added extension service of this app. ICT use in Social Science research enables accurate and reliable data collection in faster and cheaper mode. ‘e plantation survey App’ was designed and evaluated successfully for real time geo referenced data documentation, archiving and analysis.